Ghost Attendance in Digital Learning: The Phenomenon of Pseudo Attendance and Academic Participation Crisis - Nur Wahyuni (Pt. Anagata Sembagi Education, 2026)
The phenomenon of ghost attendance, or pseudo-attendance, in digital learning is a serious and increasingly prevalent issue accompanying the expansion of technology-based education. Ghost attendance occurs when students are technically registered and